2011
DOI: 10.1016/j.joca.2011.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Increased chondrocyte sclerostin may protect against cartilage degradation in osteoarthritis

Abstract: These results implicate SOST in regulating the OA disease processes, but suggest opposing effects by promoting disease-associated subchondral bone sclerosis while inhibiting degradation of cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
170
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(187 citation statements)
references
References 48 publications
13
170
4
Order By: Relevance
“…Therefore, the functional changes of chondrocytes play an important role by contributing to the degradation of the articular cartilage and thus to the pathogenesis of OA (15,16). Several studies have reported that there is a very low proliferative activity in osteoarthritic chondrocytes, which might be an efficient treatment to cure or even delay the progression of OA by promoting chondrocyte proliferation (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the functional changes of chondrocytes play an important role by contributing to the degradation of the articular cartilage and thus to the pathogenesis of OA (15,16). Several studies have reported that there is a very low proliferative activity in osteoarthritic chondrocytes, which might be an efficient treatment to cure or even delay the progression of OA by promoting chondrocyte proliferation (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…A site in question is the subchondral plate in the joints, which has been highlighted by a series of studies indicating that loss of the Wnt inhibitors is a key player in the development of osteoarthritis (178,179); however, whether this will occur with the therapeutic strategies and thereby become a potential serious side effect remains to be elucidated. In addition, nerve compression is frequently observed in osteopetrotic/osteosclerotic phenotypes (14,18,24), and in the case of the mutations related to the Wnt/LRP5 system, this is a consequence of the high bone volume.…”
Section: The Wnt/lrp5 Systemmentioning
confidence: 99%
“…This indicates a negative feedback loop wherein Wnt/β-catenin signaling in human chondrocytes played an anti-catabolic role by preventing MMP expression induced by IL-1β [88]. Another investigation also found that SOST, a potent inhibitor of canonic Wnt signaling that binds to Wnt receptor Low-density-lipoprotein receptor-related protein 5/6 (LRP5/6), inhibited further degradation of OA cartilage [89]. More recently, bone morphogenetic protein 2 (BMP-2) signaling was found to increase β-catenin nuclear translocation, LRP-5 expression, MMP levels (MMP-9, MMP-13, and MMP 14), ADAMTS-5, and collagen X expression.…”
Section: Potential Mechanisms Involved In Oa Progression and Msc Treamentioning
confidence: 92%